Metaphorical perceptions of vocational high school students on mathematical problem solving - AKKOÇ, HATİCE (My University, 2023)
Since problem solving has an important place in university level mathematics courses, determining university students' perceptions about problem solving can contribute to the field. In this regard, the aim of this study is to determine the mathematical problem solving perceptions of vocational high school students through metaphors. The case survey method was preferred for this study. Participants were 234 students studying in various programs of a vocational high school of a public university in Turkey in the fall semester of the 2019-2020 academic year. “Mathematical Problem Solving Metaphor Survey” were used as data collection tool. This survey included items that asked them to produce a metaphor for mathematical problem solving and its justification. Their written responses were analyzed using content analysis. Analysis of data indicated that participants produced 105 valid metaphors for mathematical problem solving. The most commonly used metaphors were “life”, “labyrinth”, “playing chess”, and “jigsaw puzzles”. Also, the metaphors produced by the participants were categorized under ten different conceptual categories. Metaphors were mostly gathered in the categories of “complicated” and “strategically progressive”. These categories have a statistically significant relationship with the programs in which the participants study at. Based on the categories, students’ perceptions of mathematical problem solving were discussed. Also, the study discusses instructional implications regarding how to change negative perceptions of students.

Problem çözme üniversite düzeyindeki matematik derslerinde önemli bir yere sahip olduğundan üniversite öğrencilerinin problem çözme ile ilgili algılarını belirlemek alana katkı sağlayabilir. Bu doğrultuda, bu çalışmanın amacı meslek yüksekokulu öğrencilerinin matematiksel problem çözme algılarını metaforlar aracılığıyla belirlemektir. Bunun için bu çalışmada örnek olay tarama modeli tercih edilmiştir. Araştırmanın katılımcıları 2019-2020 eğitim-öğretim yılı güz döneminde Türkiye’deki bir devlet üniversitesinin meslek yüksekokulunun çeşitli programlarında öğrenim gören 234 öğrencidir. “Matematiksel Problem Çözme Metafor Anketi” veri toplama aracı olarak kullanılmıştır. Bu ankette katılımcılardan matematiksel problem çözme ile ilgili bir metafor üretmeleri ve bunu gerekçelendirmeleri istenmiştir. Katılımcıların yazılı yanıtları içerik analizi ile analiz edilmiştir. Verilerin analizi katılımcıların matematiksel problem çözme ile ilgili 105 geçerli metafor ürettiğini göstermiştir. Katılımcıların en sık “hayat”, “labirent”, “satranç oynamak” ve “yapboz yapmak” metaforlarını ürettikleri saptanmıştır. Ayrıca katılımcıların ürettikleri metaforlar on farklı kavramsal kategori altında kategorize edilmiştir. Üretilen metaforlar en sık “komplike” ve “stratejik aşamalı” kategorilerinde toplanmıştır. Bu kategorilerin katılımcıların öğrenim gördükleri programlarla istatistiksel olarak anlamlı bir ilişkiye sahip olduğu saptanmıştır. Kategorilere dayalı olarak, öğrencilerin matematiksel problem çözme algıları tartışılmıştır. Ayrıca öğrencilerin olumsuz algılarının nasıl değiştirilebileceğine ilişkin öğretimsel çıkarımlar tartışılmıştır.